Urban housing policies with an integral approach: its implementation in Bahía Blanca (Revista Iberoamericana de Estudios Municipales, 2024)
In recent times, urban housing policies have been developed that attempt to address the problem in an integral manner. The objective of this article is to analyze those initiatives conceived under this approach that were launched in the municipality of Bahía Blanca (province of Buenos Aires, Argentina) from different state levels, using qualitative methodology. As the interventions undergo variations and reworkings when implemented in the territory, we want to evaluate to what extent they have achieved that initial aspiration and if they have not managed to get closer to that perspective, observe if the obstacles they encountered are due to limitations of the proposals themselves. itself or to local aspects. The results obtained allow us to corroborate that the comprehensive urban-housing policies applied in Bahía Blanca continue to do so in a segmented manner due to district issues, rather than due to restrictions of the regulations themselves.
Keywords: integral; urban housing policy; Local implementation regime; municipality of Bahia Blanca; state levels